State capture through indemnification demands? Effects on equity in the global distribution of COVID-19 vaccines - Ariel Gorodensky; Jillian C. Kohler (Taylor & Francis Group, 2022)
Background State capture by the pharmaceutical industry is a form of corruption whereby pharmaceutical companies shift laws or policies about their products away from the best interest of the public and toward their private benefit. State capture often limits equitable access to pharmaceutical products by inflating drug prices and increasing barriers to entry into the pharmaceutical industry. During the COVID-19 pandemic, the high demand and low supply of COVID-19 vaccines has put governments that manage vaccine procurement at risk of capture by COVID-19 vaccine manufacturers, both through bilateral deals and the COVID-19 Vaccine Global Access (COVAX) Facility; this threatens equity in the global distribution of these products. The purpose of this study is to determine whether COVID-19 vaccine manufacturers have been engaging in state capture and, if so, to examine the implications of state capture on equitable access to COVID-19 vaccines. Methods A targeted rapid literature search was conducted on state capture by the pharmaceutical industry. Results were limited to journal articles, books, and grey literature published between 2000 and 2021 in or translated to English. A literature search was also conducted for information about state capture during the COVID-19 pandemic. Results were limited to media articles published between March 2020 and July 2021 in or translated to English. All articles were qualitatively analyzed using thematic analysis. Results COVID-19 vaccine manufacturers have demanded financial indemnification from national governments who procure their vaccines. While most high-income countries are legislatively capable of indemnifying vaccine manufacturers, many low- and middle-income countries (LMICs) are not. A number of LMICs have thus changed their legislations to permit for manufacturers' indemnification demands. Amending legislation in this way is state capture and has led to delays in LMICs and vaccine manufacturers signing procurement contracts. This has critically stalled access to vaccines in LMICs and created disparities in access to vaccines between high-income countries and LMICs. Conclusions COVID-19 vaccine manufacturers' indemnification demands constitute state capture in many LMICs though not in high-income countries; this has enhanced global COVID-19 vaccine inequities. Results underscore the need to find alternatives to financial indemnification that do not hinder critical efforts to end the pandemic.